Symbolic and Iconic in Pierre’s Sociology - Hamad, Esaaf (Al-Adab Journal, 2021)
This paper discusses two concepts within Pierre Bourdieu’s sociological system that are; symbol and icon in their functional exchange and their procedural meanings that are involved in his system and how they can be interpreted to give more understanding for new nature of sociology that Bourdieu seeks to dress it. The present paper raises the question, starting point, about the meaning of sociology, the way Bourdieu wanted. Bourdieu asked about the nature of fields or domains that sociology deals with from one side, and on the other hand, the question about the unique features that give sociology its peculiar topic apart from other sciences. The present paper shed lights on the relationship between natural and historical in sociology and how historical was replaced for the favor of natural. This replacement was marketed as a scientific endvour. In the second stage of study, understanding is given to explain what is symbolic and what is iconic and how material turned to be socially symbolic and how social and institutions became iconic everlasting. Finally, this paper seeks to shed a critical view on Bourdieu,s sociological account in respect to his reading of both symbol and icon.